(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
In the article on the basis of rich factual material, some aspects of the protection and use of historical and cultural monuments of the Fergana region, the attitude to them during the Soviet regime and in the years of independence are revealed.